Tindak Pidana Penipuan Melalui Aplikasi Digital (Gagasan Pemikiran Pertanggungjawaban Oleh Bank) - Elisa Putri, Dina; Sudarti, Elly; Siregar, Elizabeth (Faculty of Law, Universitas Jambi, 2024)
The aim of this research is 1) to determine and analyze the regulations for criminal acts of fraud through digital applications, and 2) the form of bank criminal liability for criminal acts of fraud through digital applications. The type of research is normative juridical. The research results show that regulation of criminal acts of fraud through digital applications can be guided by Article 492 and Article 263 of the new Criminal Code as well as Article 28 paragraph (1) of the ITE Law. However, in the regulation there is still a blurring of norms because Article 378, Article 492 and Article 263 of the Criminal Code as well as Article 28 paragraph (1) of the ITE Law also do not specifically emphasize the proportion of